Spinal intradural extramedullary mature cystic teratoma in young adult: a rare tumor with review of literature - Agay, Ashuvi Kunjan; Garg, Sunil; Hedaoo, Ketan (International Journal of Research in Medical Sciences, 2016)
Spinal intradural extramedullary teratoma is a rare condition that develops more commonly in children than in adults. We report a rare case of adult onset intradural extramedullary teratoma in the thoracolumbar spinal cord with no evidence of spinal dysraphism and without the history of prior spinal surgery. The patient was a 20 year young adult male whose chief complaint was back pain and urinary incontinence. X-ray images of the thoraco-lumbar spine showed no abnormalities. Magnetic resonance imagings of spine revealed a well marginated cystic intradural extramedullary mass at the D11 to D12 vertebral levels. The patient was operated and the mass was totally excised. It was histopathologically diagnosed as a mature cystic teratoma. The patient's symptom of back pain and urinary incontinence was improved following the surgery.